Pendidikan Siaga Bencana melalui Pembelajaran Integratif bagi Siswa SD - Pranajati, Nindya Rachman (Al-Azkiya: Jurnal Pendidikan MI/SD, 2022)
This research aimed to analyze implement disaster preparedness education through integrative learning on elementary schools and the obstacles in implementing it. This research was a qualitative research. Data was collected using the methods of observation, interviews, and documentation. Analysis of the data using the theory of Miles and Huberman, namely by reducing data, displaying data, and drawing conclusions. The results showed that the two schools linked disaster preparedness materials in the main subjects, so they did not stand as separate subjects. There were differences in the mapping of material aspects, even though the two schools present material on disasters, but they were adjusted to see the potential for natural disasters that occur in their respective regions. The material aspects presented in both schools were disaster knowledge, threats from disasters, disasters viewed from several aspects, and anticipatory actions to reduce the risks caused. Implementation refered to the parameters of disaster preparedness, namely school policies, building knowledge and attitudes through integrative learning, making emergency response plans and early warnings that had been mutually agreed upon, and maximizing the mobilization of existing resources in schools to achieve disaster preparedness goals